2004
DOI: 10.1074/jbc.m405789200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Type 1 Forms a Complex with the Transient Outward Potassium Channel Kv4.3 and Regulates Its Gating Properties and Intracellular Localization

Abstract: We report a novel signal transduction complex of the angiotensin receptor type 1. In this complex the angiotensin receptor type 1 associates with the potassium channel ␣-subunit Kv4.3 and regulates its intracellular distribution and gating properties. Electrophysiological remodeling in hypertrophy and heart failure predisposes the heart to lethal arrhythmias, which account for half of the mortality (1, 2). Experimental evidence derived from large scale clinical trials shows that inhibition of angiotensin II sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 47 publications
(49 reference statements)
2
70
0
Order By: Relevance
“…Interestingly, it has also been reported that the angiotensin receptor interacts directly with K V 4.3 and modulates the gating and internalization of K V 4.3-encoded I to channels. 17 Taken together, these findings indicate a role for post-translational remodeling of Ca V and K V channels (possibly regulated through angiotensin) in short-term cardiac memory ( Fig. 2), with the additional involvement of Na V channel remodeling in human ventricles.…”
Section: Ion Channel Remodeling In Short-term Cardiac Memorymentioning
confidence: 68%
“…Interestingly, it has also been reported that the angiotensin receptor interacts directly with K V 4.3 and modulates the gating and internalization of K V 4.3-encoded I to channels. 17 Taken together, these findings indicate a role for post-translational remodeling of Ca V and K V channels (possibly regulated through angiotensin) in short-term cardiac memory ( Fig. 2), with the additional involvement of Na V channel remodeling in human ventricles.…”
Section: Ion Channel Remodeling In Short-term Cardiac Memorymentioning
confidence: 68%
“…Angiotensin receptor forms a complex with potassium channel alphasubunit Kv 4.3 and regulates its intracellular distribution and gating properties [7]. Dihydropyridine Ca2+ channel antagonists / agonists may block Kv4.2, Kv4.3 and Kv1.4 K+ channels expressed in HEK293 cells [8].…”
Section: Kcnd3mentioning
confidence: 99%
“…Enhancement of the Kv4.3 current by tyrosine kinase is similar to KCNQ1 and opposite to Kv1.2 and Kv1.5. With respect to endocytosis, activation of AT 1 R was reported to suppress the Kv4.3 current through internalization of the receptor and channel complex (24). Kv4.3 has a β-subunit KChIP2 that enhances delivery of Kv4.3 to the cell surface.…”
Section: Kv43mentioning
confidence: 99%